Apixaban versus No Anticoagulation in Patients Undergoing Long-Term Dialysis with Incident Atrial Fibrillation - Mavrakanas, Thomas A. (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: The relative efficacy and safety of apixaban compared with no anticoagulation have not been studied in patients on maintenance dialysis with atrial fibrillation. We aimed to determine whether apixaban is associated with better clinical outcomes compared with no anticoagulation in this population. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This retrospective cohort study used 2012–2015 US Renal Data System data. Patients on maintenance dialysis with incident, nonvalvular atrial fibrillation treated with apixaban (521 patients) were matched for relevant baseline characteristics with patients not treated with any anticoagulant agent (1561 patients) using a propensity score. The primary outcome was hospital admission for a new stroke (ischemic or hemorrhagic), transient ischemic attack, or systemic thromboembolism. The secondary outcome was fatal or intracranial bleeding. Competing risk survival models were used. RESULTS: Compared with no anticoagulation, apixaban was not associated with lower incidence of the primary outcome: hazard ratio, 1.24; 95% confidence interval, 0.69 to 2.23; P=0.47. A significantly higher incidence of fatal or intracranial bleeding was observed with apixaban compared with no treatment: hazard ratio, 2.74; 95% confidence interval, 1.37 to 5.47; P=0.004. A trend toward fewer ischemic but more hemorrhagic strokes was seen with apixaban compared with no treatment. No significant difference in the composite outcome of myocardial infarction or ischemic stroke was seen with apixaban compared with no treatment. Compared with no anticoagulation, a significantly higher rate of the primary outcome and a significantly higher incidence of fatal or intracranial bleeding and of hemorrhagic stroke were seen in the subgroup of patients treated with the standard apixaban dose (5 mg twice daily) but not in patients who received the reduced apixaban dose (2.5 mg twice daily). CONCLUSIONS: In patients with kidney failure and nonvalvular atrial fibrillation, treatment with apixaban was not associated with a lower incidence of new stroke, transient ischemic attack, or systemic thromboembolism but was associated with a higher incidence of fatal or intracranial bleeding. PODCAST: This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2020_05_29_CJN11650919.mp3